Building Safe and Inclusive Schools: Enhancing Anti-Bullying Awareness Based On The Sustainable Development Goals (SDGs) Agenda At MAN 2 Cianjur - Septiyana, Iyan; Mellani; Sani, Talitha Azmi (Journal of Community Services and Engagement: Voice of Community (VOC), 2025)
Bullying in schools is a social phenomenon that occurs throughout Indonesia, including in Cianjur Regency, West Java Province. Quality Education is part of the UN Sustainable Goals agenda that required to be implemented by member states, including Indonesia. The priority issue underlying this activity is the continued prevalence of bullying due to a lack of understanding and knowledge about the SDGs. As a solution, the community service team held a public lecture and workshop with the theme "Safe and Inclusive Schools: Building Anti-Bullying Awareness." The implementation method included interactive education through material presentations, student group discussions, reflections, and the preparation of written commitments by students. The results of the implementation showed high enthusiasm and active participation from the 100 students who participated. They demonstrated the ability to think reflectively and empathetically and were able to formulate a collective commitment to creating a bullying-free school, highlighting their shared responsibility and determination.